PREVALENSI GERD DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA - E. Amirul Haiban Syah (2023)
The prevalence of Gastroesophageal Reflux Disease (GERD) in Indonesia ranges between 9.35-25.18%. GERD risk factors consist of non-modifiable factors such as age, gender and genetic factors, as well as modifiable factors such as lifestyle, diet and body weight. Given the dense lecture activities of medical students, their lifestyle is not maintained, especially dietary habits which can increase the risk of developing GERD. The purpose of this study is to measure the prevalence and risk factors for GERD in medical students of UPN "Veteran" Jakarta. This study is an observational analytic study with a cross-sectional design. A sample of 149 respondents was taken by stratified random sampling. The questionnaire used contains risk factors and eating habits to assess factors that affect GERD, as well as the GERD Questionnaire (GERD-Q) to assess GERD symptoms. Analysis was performed by the Chi-Square test and logistic regression test. The prevalence of GERD in medical students of UPN "Veteran" Jakarta was 7.4% and there were significant results between the habit of skipping breakfast (P = 0.023) and GERD symptoms. The habit of skipping breakfast can occur due to clashes between lecture schedules and breakfast time, triggering stomach acid exacerbations, which can cause stomach acid reflux and GERD to occur.